Equivalence Strategies Of Simple Sentences Used In Detective Conan Comic - Ningrum, Alfi Wahyu; , Dr. Dwi Haryanti, M.Hum; , Mauly Halwat Hikmat, Ph. D (2014)
This research belongs to descriptive qualitative research, aiming at identifying and categorizing the variations of translation of simple sentence found in Detective Conan comic; verifying strategies used; and portraying the accuracy of the translation. The data are simple sentences found in Detective Conan comic. The data collected from document and informant, then, are analyzed using Baker's theory of equivalence. The findings of the research are: (1) there are 5 translation variations of simple sentence, i.e. simple sentence translated into (a) simple sentence; (b) complex sentence; (c) minor sentence; (d) two sentences; and (e) not sentence; (2) there are 6 strategies used, i.e. (a) addition; (b) omission; (c) structural adjustment; (d) adoption; (e) adaptation; and (e) paraphrase, as the most dominant strategy used; and (3) the translation is categorized as accurate with 99.4% rate or out of 182 data analyzed, there are 181 data accurately translated and 1 datum inaccurately translated.